O passo em falso na dança da subjetivação: o transtorno de subjetivação arcaica e sua abordagem na clínica psicanalítica - Metzner, Carla Braz (2021)
This study aims to investigate possible issues on the cornerstone of psychic constitution, which may lead to psychological suffering and trauma, together with symptoms manifested in interactions, communication and in the way one can play. We were initially guided by the approach of the psychoanalyst Vitor Guerra, who believes the link between the nascent subject and the primary objects is a gradual co-construction, which occurs through a rhythm and Access to intersubjectivity. Two clinical cases show that the steps of the nascent subject and the primary objects may go out of sync, leading to a false step in the dance of subjectivation, which would be key to the experience of internal continuity and psychic integration. By contemplating the reception and the work with the primary bonds and the subjectifying environment in order to rediscover the rhythm of joint sharing, this approach opposes the current classifying trend of diagnoses